1428. Modeling Reductions in Antibiotic Prescriptions due to Otitis Media in Canada as a Result of Pneumococcal Conjugate Vaccination. (26th November 2018) - Breton, Marie-Claude; Farkouh, Raymond; Vojicic, Jelena; Wilson, Michele; McDade, Cheryl; Wasserman, Matt
Abstract: Background: Vaccines are an important factor in combating the growing global health issue of antimicrobial resistance. Pneumococcal conjugate vaccines (PCVs) have substantially reduced the burden of otitis media (OM) caused by S. pneumoniae, one of the largest causes of antibiotic prescriptions (Abx) in children under 5. The purpose of this study was to quantify the number of Abx avoided since the introduction of a national PCV program in Canada. Methods: We adapted a previously published forecasting model to estimate the reduction in OM cases in Canada since the introduction of PCVs in all routine provincial programs in 2005 through 2015 (the last year complete data were available). The impact of PCV on OM was modeled and compared with pre-PCV incidence to estimate net impact of the vaccine. We assumed that 90% of OM episodes were treated with an initial Abx given routine practice. All data were sourced from the published literature. Results: Over 10 years, PCVs were estimated to avert 3.7 million cases of OM in Canada. This corresponded to an estimated reduction of 3.3 million Abx, or 0.96 Abx avoided per infant vaccinated with PCV. Conclusion: PCVs have had a significant public health impact on reducing the burden of disease and Abx. While most of the PCV impact on reduction of Abx is due to reduction in OM cases, additional Abx reduction from prevention of other invasive and noninvasive pneumococcal diseases is of importance. Further research is necessary to understand the additional net benefit of reducing antibiotics across the disease spectrum given that reductions in net prescribing could avert further downstream resistance by other pathogens. Disclosures: M. C. Breton, Pfizer inc.: Employee, Salary. R. Farkouh, Pfizer: Employee, Salary. J. Vojicic, Pfizer: Employee and Shareholder, Benefits and stock and Salary. M. Wilson, Pfizer Inc: Consultant, Consulting fee. C. McDade, Pfizer Inc.: Consultant, Consulting fee. M. Wasserman, Pfizer: Employee, Salary.